Structure and diversity of the piedmont scrub adjacent to the metropolitan area of Monterrey, Nuevo León, Mexico - Alanís-Rodríguez, Eduardo; Jiménez-Pérez, Javier; Mora-Olivo, Arturo; Martínez-Ávalos, José Guadalupe; Mata-Balderas, José Manuel; Chávez-Costa, Alejandro Collantes; Rubio-Camacho, Ernesto A. (Instituto de Ecología, A.C., 2015)
In this study the structure and diversity of the piedmont scrub that abuts the western portion of the metropolitan area of Monterrey, Mexico, were examined. Vegetation composition and diversity were assessed by sampling vegetation in 41 plots of 100 m2 each. All trees and shrubs with a basal diameter (d0.10) ≥0.5 cm were counted, including succulents. In addition, the crown diameter (dcrown) for each species was recorded. Species richness was assessed by means of the Margalef index (DMg), while Shannon’s index (H’) was used to assess species diversity. A total of 45 species, 39 genera and 18 families were recorded. Fabaceae was the most important family with the highest species richness (12), followed by Cactaceae (5), Euphorbiacae, Rhamnaceae, Rutaceae and Verbenaceae (3); these families accounted for 64.44% of the entire flora recorded in the area. As for dominance (Dr), Fabaceae, Rutaceae, Asteraceae and Verbenaceae accounted for 64.08% of the Importance Value Index (IVI) in the community. The scrub presented a density of 3629 ind./ha-1 and a total crown cover of 6629 m2/ha-1. Acacia amentacea and Zanthoxylum fagara were the most important species, since they accounted for 25.87% of the IVI values in the locality. The rank/abundance curve for species fitted best to a log-normal function, which is characteristic of mature communities. The present study shows that the studied community is characterized by a high diversity and species richness in comparison to other arid and semi-arid climate vegetation in Northeast Mexico. Structural and diversity attributes documented in this study indicated that the piedmont scrub neighboring Monterrey is a well-preserved community in a mature successional stage; hence, it is urgent to develop strategies aimed at its conservation.